2020
DOI: 10.1002/cphc.202000720
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Diminutive Effects between Regium and Aerogen Bonds

Abstract: The aerogen bond is formed in complexes of HCN−XeF2O and C2H4−XeF2O. The lone pair on the N atom of HCN is a better electron donor in the aerogen bond than the π electron on the C=C bond of C2H4. The coinage substitution strengthens the aerogen bond in MCN−XeF2O (M=Cu, Ag, and Au) and its enhancing effect becomes larger in the Au Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Unfortunately, this work did not delve into the σ or π-hole depths as background information. [111]. The σ-hole was able to interact with a N lone pair as well as the unsaturated π-system of a C=C bond.…”
Section: σ- Hole and π-Hole On The Same Atommentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, this work did not delve into the σ or π-hole depths as background information. [111]. The σ-hole was able to interact with a N lone pair as well as the unsaturated π-system of a C=C bond.…”
Section: σ- Hole and π-Hole On The Same Atommentioning
confidence: 99%
“…where M= Cu, Ag or Au [111]. The σ-hole was able to interact with a N lone pair as well as the unsaturated πsystem of a C=C bond.…”
Section: σ- Hole and π-Hole On The Same Atommentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Seven years ago, a possible extension of this mindset to dblock elements was considered [6] and subsequently confirmed, first for elements of Group 11, [7] and then for elements of Groups 10 [8] and 12. [9] Various theoretical studies, [10][11][12][13] and a more limited number of experimental findings, [14,15] have shown that nanoparticles [16] and halide salts [14] of Cu, Ag, and Au form attractive interactions with a variety of donors of electron density by involving the regions with the most positive electrostatic potential at their outer surface. It has been proposed that such interactions involving Group 11 elements should be designated as regium bonds [10] or coinage bonds.…”
mentioning
confidence: 99%
“…[9] Various theoretical studies, [10][11][12][13] and a more limited number of experimental findings, [14,15] have shown that nanoparticles [16] and halide salts [14] of Cu, Ag, and Au form attractive interactions with a variety of donors of electron density by involving the regions with the most positive electrostatic potential at their outer surface. It has been proposed that such interactions involving Group 11 elements should be designated as regium bonds [10] or coinage bonds. [13] Herein we report experimental and theoretical results that show that not only gold in neutral species, as mentioned above, but also gold in negatively charged species can function as an acceptor of electron density, namely, be a coinage-bond (CiB) donor.…”
mentioning
confidence: 99%